2020
DOI: 10.3390/ani10122395
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data from Six Years of Selective Anthelmintic Treatment on Five Horse Farms in France and Switzerland

Abstract: Anthelmintic resistance (AR) of small strongyle populations (cyathostomins) against products of the benzimidazole and tetrahydropyrimidine classes occurs now worldwide and there is an increasing number of reports also regarding macrocyclic lactones. Consequently, and in order to maintain an appropriate horse parasite control, alternative control schemes must be evaluated under field conditions. Here we present a six-year field study on the administration of the so-called selective or targeted selective anthelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The latter results are in the same range with those recently reported in a study of five horse farms in Western Switzerland and France (34.7%) (Roelfstra et al, 2020). As only a small data volume was available for the Italian-speaking region (canton Ticino), no statistical analysis was done here.…”
Section: Discussionsupporting
confidence: 88%
“…The latter results are in the same range with those recently reported in a study of five horse farms in Western Switzerland and France (34.7%) (Roelfstra et al, 2020). As only a small data volume was available for the Italian-speaking region (canton Ticino), no statistical analysis was done here.…”
Section: Discussionsupporting
confidence: 88%
“…Targeted selective treatment (TST) is based on the 80:20 over‐dispersion rule, where it has been shown that in adult horse populations 20% of the animals harbour 80% of the parasites 33 . Low shedding horses tend to shed consistently low number of cyathostomin eggs over time 34,35 and TST has been shown to reduce the need for anthelmintics and reduce the costs associated with parasite control 36–38 . A risk factor analysis based on FECRT data from 688 horses on 39 French horse farms and riding schools indicated that FEC‐based treatment regimens combined with individual anthelmintic dosage and the enforcement of tighter biosecurity around horse introduction resulted in a significant reduction in risk of drug resistance (relative risk of 0.57) 39 …”
Section: Resultsmentioning
confidence: 99%
“…33 Low shedding horses tend to shed consistently low number of cyathostomin eggs over time 34,35 and TST has been shown to reduce the need for anthelmintics and reduce the costs associated with parasite control. [36][37][38] A risk factor analysis based on FECRT data from 688 horses on 39 French horse farms and riding schools indicated that FEC-based treatment regimens combined with individual anthelmintic dosage and the enforcement of tighter biosecurity around horse introduction resulted in a significant reduction in risk of drug resistance (relative risk of 0.57). 39 Modelling studies (which assumed little or no resistance at the outset) highlight a number of environmental and treatment factors that significantly impact the speed of development of resistance in relation to TST approaches:…”
Section: Does Targeted Selective Treatment Slow the Spread Of Anthelm...mentioning
confidence: 99%
“…Therefore, targeted selective treatment, a strategy that has been advocated by parasitologists for two decades, is increasingly being implemented on Swedish equestrian premises. By only treating horses exceeding a chosen cut-off value, often 200 strongyle eggs per gram of faeces (EPG), markedly fewer anthelmintic treatments are administered, increasing the chance of slowing down the development and spread of anthelmintic resistance [ 6 , 7 , 8 , 9 ]. In addition, to reduce exposure to infective larvae on pasture, preventive control methods using various pasture-management methods are also recommended.…”
Section: Introductionmentioning
confidence: 99%